Acceptability of Acute and Maintenance Pharmacotherapy of Bipolar Disorder: A Systematic Review of Randomized, Double-Blind, Placebo-Controlled Clinical Trials. Issue 2 (March 2020) - Bai, Yuanhan; Yang, Haichen; Chen, Guanjie; Gao, Keming
Abstract: Purpose/Background: The aim of the study was to estimate and rank the risk for the discontinuation due to adverse events (DAEs), 7% or more weight gain (WG), and somnolence during the acute and maintenance treatment of bipolar disorder with a mood stabilizer or an antipsychotic monotherapy. Methods/Procedures: The search of MEDLINE, EMBASE, PsycINFO, and clinicaltrials.gov from the inception to December 31, 2018, provided 32 studies in mania, 16 in bipolar depression, and 13 in maintenance. Data of DAEs, WG, and somnolence from each study were extracted. The risk for these variables of an active treatment relative to placebo was estimated with a number needed to harm (NNH) as a single study and pooled sample. Findings/Results: For DAEs, pooled NNH ranged from 19 with carbamazepine to −21 with quetiapine-XR in mania, 11 with quetiapine-IR 600 mg/d to −37 with olanzapine/fluoxetine combination in bipolar depression, and 5 with lithium to −8 with asenapine in maintenance. For WG, pooled NNH ranged from 9 with olanzapine to −78 with aripiprazole in mania, 5 with olanzapine to −112 with lithium in bipolar depression, and 4 with olanzapine to 126 with asenapine in maintenance. For somnolence, pooled NNH was from 5 with carbamazepine to 23 with cariprazine in mania, 3 with quetiapine-XR 300 mg/d to 79 with lurasidone in bipolar depression, and 11 with olanzapine to −49 with aripiprazole in maintenance. Implications/Conclusions: All medications studied in bipolar disorder were relatively well tolerated during different phases of treatment; however, the risk for short- and long-term WG and somnolence varied widely among included psychotropics. Abstract : Supplemental digital content is available in the text.